PENGARUH LITERASI KEUANGAN SYARI’AH DAN PEMBAYARAN DIGITAL (E-WALLET) TERHADAP PENINGKATAN OMZET USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PADA KELURAHAN GEDUNG JOHOR - Riki Gunawan; Arifa Pratami; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Thi~s stud~y ai~ms to analyze~ the~ i~nflue~nce~ of I~slami~c fi~nanci~al li~te~racy and~ d~i~gi~tal payme~nt (e~-walle~t) on i~ncre~asi~ng the~ turnove~r of Mi~cro, Small, and~ Me~d~i~um E~nte~rpri~se~s (MSME~s) i~n Ge~d~ung Johor Vi~llage~. Thi~s re~se~arch i~s moti~vate~d~ by the~ i~mportance~ of shari~a-base~d~ fi~nanci~al manage~me~nt and~ the~ uti~li~zati~on of d~i~gi~tal payme~nt te~chnology to support busi~ne~ss d~e~ve~lopme~nt i~n the~ d~i~gi~tal e~ra. Thi~s stud~y e~mploye~d~ a quanti~tati~ve~ approach wi~th an associ~ati~ve~ re~se~arch d~e~si~gn. The~ populati~on i~n thi~s stud~y consi~ste~d~ of 110 MSME~ actors, wi~th a sample~ of 86 re~spond~e~nts d~e~te~rmi~ne~d~ usi~ng the~ Slovi~n formula and~ purposi~ve~ sampli~ng te~chni~que~. D~ata we~re~ colle~cte~d~ through que~sti~onnai~re~s usi~ng a Li~ke~rt scale~ and~ analyze~d~ usi~ng vali~d~i~ty te~sts, re~li~abi~li~ty te~sts, classi~cal assumpti~on te~sts, multi~ple~ li~ne~ar re~gre~ssi~on analysi~s, t-te~st, F-te~st, and~ coe~ffi~ci~e~nt of d~e~te~rmi~nati~on. The~ re~sults showe~d~ that parti~ally, I~slami~c fi~nanci~al li~te~racy had~ a posi~ti~ve~ and~ si~gni~fi~cant e~ffe~ct on i~ncre~asi~ng MSME~ turnove~r, wi~th a t-count of 5.912 > t-table~ of 1.989 and~ a si~gni~fi~cance~ value~ of 0.000 < 0.05, whi~le~ d~i~gi~tal payme~nt (e~-walle~t) also had~ a posi~ti~ve~ and~ si~gni~fi~cant e~ffe~ct on i~ncre~asi~ng MSME~ turnove~r, wi~th a t-count of 4.668 > t-table~ of 1.989 and~ a si~gni~fi~cance~ value~ of 0.000 < 0.05. Si~multane~ously, I~slami~c fi~nanci~al li~te~racy and~ d~i~gi~tal payme~nt (e~-walle~t) had~ a posi~ti~ve~ and~ si~gni~fi~cant e~ffe~ct on i~ncre~asi~ng MSME~ turnove~r, wi~th an F-count of 31.816 > F-table~ of 3.105 and~ a si~gni~fi~cance~ value~ of 0.000 < 0.05. The~ coe~ffi~ci~e~nt of d~e~te~rmi~nati~on (R²) of 0.434 i~nd~i~cate~s that 43.4% of the~ vari~ati~on i~n MSME~ turnove~r i~ncre~ase~ can be~ e~xplai~ne~d~ by the~se~ two vari~able~s, whi~le~ the~ re~mai~ni~ng 56.6% i~s i~nflue~nce~d~ by othe~r factors outsi~d~e~ thi~s stud~y. Thus, i~mprovi~ng I~slami~c fi~nanci~al li~te~racy and~ opti~mi~zi~ng the~ use~ of e~-walle~ts can be~ i~mportant factors i~n e~ncouragi~ng the~ i~ncre~ase~ of MSME~ turnove~r i~n Ge~d~ung Johor Vi~llage~.